Functional regulatory T cells produced by inhibiting cyclic nucleotide phosphodiesterase type 3 prevent allograft rejection. - Feng, G; Nadig, SN; Bäckdahl, L; Beck, S; Francis, R; Schiopu, A; Whatcott, A; Wood, K; Bushell, A (2011)
Regulatory T cells (T(regs)) manipulated ex vivo have potential as cellular therapeutics in autoimmunity and transplantation. Although it is possible to expand naturally occurring T(regs), an attractive alternative possibility, particularly suited to solid organ and bone marrow transplantation, is the stimulation of total T cell populations with defined allogeneic antigen-presenting cells (APCs) under conditions that lead to the generation or expansion of donor-reactive, adaptive T(regs). Here we demonstrate that stimulation of mouse CD4(+) T cells by immature allogeneic dendritic cells combined with pharmacological inhibition of phosphodiesterase 3 (PDE) resulted in a functional enrichment of Foxp3(+) T cells. Without further manipulation or selection, the resultant population delayed skin allograft rejection mediated by polyclonal CD4(+) effectors or donor-reactive CD8(+) T cell receptor transgenic T cells and inhibited both effector cell proliferation and T cell priming for interferon-γ production. Notably, PDE inhibition also enhanced the enrichment of human Foxp3(+) CD4(+) T cells driven by allogeneic APCs. These cells inhibited T cell proliferation in a standard in vitro mixed lymphocyte assay and, moreover, attenuated the development of vasculopathy mediated by autologous peripheral blood mononuclear cells in a functionally relevant humanized mouse transplant model. These data establish a method for the ex vivo generation of graft-reactive, functional mouse and human T(regs) that uses a clinically approved agent, making pharmacological PDE inhibition a potential strategy for T(reg)-based therapies.